2017
DOI: 10.7567/jjap.57.011301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dose and size on defect engineering in carbon cluster implanted silicon wafers

Abstract: REGULAR PAPERS • OPEN ACCESSEffect of dose and size on defect engineering in carbon cluster implanted silicon wafers Carbon-cluster-ion-implanted defects were investigated by high-resolution cross-sectional transmission electron microscopy toward achieving high-performance CMOS image sensors. We revealed that implantation damage formation in the silicon wafer bulk significantly differs between carbon-cluster and monomer ions after implantation. After epitaxial growth, small and large defects were observed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…However, Okuyama et al reported that the HRTEM observation results they obtained for the carbon cluster ion implantation projection range in silicon wafers showed no extended defects such as dislocations and dislocation loops in range after heat treatment. Moreover, by using electron diffraction defect analysis, they observed single‐electron diffraction pattern, which indicate that Si‐C agglomeration was not induced after heat treatment.…”
Section: Resultsmentioning
confidence: 98%
“…However, Okuyama et al reported that the HRTEM observation results they obtained for the carbon cluster ion implantation projection range in silicon wafers showed no extended defects such as dislocations and dislocation loops in range after heat treatment. Moreover, by using electron diffraction defect analysis, they observed single‐electron diffraction pattern, which indicate that Si‐C agglomeration was not induced after heat treatment.…”
Section: Resultsmentioning
confidence: 98%
“…The TEM images in the C 3 H 6 -ion-implanted region of both wafers only showed defects 5 nm in size. These defects were also observed in a monomer-ion-implanted Si wafer and hydrocarbon-molecular-ion-implanted Si wafer after heat treatment [ 36 , 37 ]. It has been reported that the 5 nm defects are agglomerates consisting of C and I (C– I agglomerates), and those defects act as gettering sinks for metallic impurities [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…These defects were also observed in a monomer-ion-implanted Si wafer and hydrocarbon-molecular-ion-implanted Si wafer after heat treatment [ 36 , 37 ]. It has been reported that the 5 nm defects are agglomerates consisting of C and I (C– I agglomerates), and those defects act as gettering sinks for metallic impurities [ 37 ]. It is considered that Cu and Ni gettering in the C 3 H 6 -ion-implanted region of both single and double epitaxial Si wafers shown in Figure 5 occurred through this type of defect.…”
Section: Resultsmentioning
confidence: 99%
“…The projected range of less than 4 nm was reached at the energy of 1 keV. In another study carbon clusters such as C 3 H 5 and C 2 H 5 have been used for special shallow defect formation in silicon; such defects possessing high gettering capability for metal ions can improve CMOS image sensor parameters …”
Section: Introductionmentioning
confidence: 99%
“…In another study carbon clusters such as C 3 H 5 and C 2 H 5 have been used for special shallow defect formation in silicon; such defects possessing high gettering capability for metal ions can improve CMOS image sensor parameters. 13 Nowadays, SiC is studied as a material for high-voltage and hightemperature applications, due to its wide band gap, high thermal conductivity, and large breakdown electric field. 14,15 However, thermal diffusion doping requires temperatures higher than 1700°C because of the very low diffusion coefficients of impurities.…”
Section: Introductionmentioning
confidence: 99%